The role of self-control in predicting college adjustment among first-year psychology students - Etia Intana; Hartosujono Hartosujono; Haniek Farida (Universitas Ahmad Dahlan, 2026)
Student adaptation during the early transition to higher education is a critical aspect closely related to academic success, social functioning, and psychological well-being. Based on Self-Regulation Theory and the Theory of Student Adjustment, self-control is conceptualized as a key psychological factor that contributes to successful student adaptation. This study aimed to examine the relationship between self-control and college adjustment among first-year psychology students at Universitas Sarjanawiyata Tamansiswa. A quantitative approach with a cross-sectional correlational design was employed. A total of 98 first-semester students participated in the study and were selected using purposive sampling. Data were collected using a Self-Control Scale and a Student Adjustment Scale with established validity and reliability. Data analysis was conducted using Pearson Product-Moment correlation. The results revealed a significant positive relationship between self-control and student adjustment, r(96) = 0.772, p < 0.001. These findings indicate that students with higher levels of self-control tend to demonstrate better adaptation in dealing with academic, social, personal-emotional, and institutional demands during the transition to university. This study provides empirical support for the role of self-regulation in student adjustment processes and highlights the importance of developing self-control enhancement programs to support successful adaptation among first-year university students.